Synthesis and Characterization of Graphene Using Coconut Shell Charcoal - Sholehah, Amalia; Vinanza, Naufal Eka; Huda, Nurul; Rengga, Wara Dyah Pita (Universitas Negeri Semarang, 2020)
Coconut shell waste has great potential as a source of carbon in the future. Graphite is one of the carbon allotropes with layers of planar layered carbon atoms. One layer of graphite is called graphene with hexagonal carbon atomic structure. In this study, the Hummers method was used to obtain graphene from coconut shell waste. This method breaks the bonding graphite layer into graphene by utilizing the process of mixing a mixture of graphite and HCl solution with the addition of KMnO4 and NaNO3. Raman Spectroscopy characterization shows the formation of multilayer graphene with D, G, and 2D values in 1365, 1585, and 2865 cm-1. The Fourier Transform Infrared Spectroscopy characterization confirmed the bonds of C-O, C = C and C = O at 1220, 1580, and 1700 cm-1. Meanwhile, X-Ray Diffraction characterization showed a peak of diffraction of graphene at 2ÃŽÂ¸ at 11.6o; 23.9o; and 43.5o. The graphene produced becomes more transparent with the length of time of stirring, and the smaller the size of the graphite particles results in the irregularity of the graphene crystal structure.